RELATIONSHIP BETWEEN FIBER MORPHOLOGY AND PARALLEL-TO-GRAIN MECHANICAL STRENGTH IN FOUR BAMBOO SPECIES GROWNIN THE PHILIPPINES - Oliver S. Marasigan; Mario Angelo M. Mundn; Shereyl A. Daguinod; Emmanuel P. Domingo; Jayric F. Villareal (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTSThe study evaluated the fiber morphology and mechanical properties of four bamboo species, revealing the species-specific relationships of fiber traits and mechanical performance.Cell wall thickness and lumen width influenced bamboo’s mechanical strength. Solid bamboo exhibits the highest compression despite weak fiber links; Yellow bamboo displays the highest shear with the longest fibers; Thailand bamboo demonstrates the strongest fiber traits-strength correlations.ABSTRACTThe compression and shear strength parallel to the grain of four bamboo species namely Yellow bamboo (Bambusa vulgaris Schrad. ex J.C.Wendl.), Iron bamboo (Guadua angustifolia Kunt.), Solid bamboo [Dendrocalamus strictus (Roxb.) Nees], and Thailand bamboo (Thyrsostachys siamensis Gamble) were evaluated in relation to their fiber morphology. Results revealed distinct species-specific patterns. Thailand bamboo exhibited the strongest positive correlations, particularly between fiber length, fiber diameter, cell wall thickness, and both strength properties. Yellow bamboo recorded the longest fibers and the highest shear strength, with strong associations to cell wall thickness. In contrast, Solid bamboo showed the highest compression strength but weak correlations with fiber characteristics, while Iron bamboo demonstrated moderate associations between fiber morphology and mechanical properties. Among all fiber characteristics, cell wall thickness consistently showed a strong positive correlation with strength across species, whereas lumen width was negatively correlated, indicating that denser, more compact fiber structures enhance load-bearing capacity. Principal Component Analysis further confirmed the dominant influence of cell wall thickness, with variable contributions from fiber length and diameter depending on species. These findings highlight the anatomical basis of bamboo’s mechanical performance and emphasize the need for species-specific approaches in its structural utilization.